2016
DOI: 10.1113/jp271229
|View full text |Cite
|
Sign up to set email alerts
|

Symmorphosis and skeletal muscle : in vivo and in vitro measures reveal differing constraints in the exercise‐trained and untrained human

Abstract: Key pointsr The concept of symmorphosis predicts that the capacity of each step of the oxygen cascade is attuned to the task demanded of it during aerobic exercise at maximal rates of oxygen consumption (V O 2 max ) such that no single process is limiting or in excess atV O 2 max .r The present study challenges the applicability of this concept to humans by revealing clear, albeit very different, limitations and excesses in oxygen supply and consumption among untrained and endurance-trained humans.r Among untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
104
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 41 publications
(74 reference statements)
6
104
2
1
Order By: Relevance
“…The observed dysmorphosis in trained subjects by Gifford et al (2) was not confirmed in our larger sample containing a wider range of V O 2 max (5). We did not intend to suggest that Gifford et al (2) based their results, challenging symmorphosis, on only four subjects.…”
contrasting
confidence: 92%
See 1 more Smart Citation
“…The observed dysmorphosis in trained subjects by Gifford et al (2) was not confirmed in our larger sample containing a wider range of V O 2 max (5). We did not intend to suggest that Gifford et al (2) based their results, challenging symmorphosis, on only four subjects.…”
contrasting
confidence: 92%
“…We did not intend to suggest that Gifford et al (2) based their results, challenging symmorphosis, on only four subjects. In our view, six of the trained subjects fitted the (extrapolated) relationship between V O 2 max and mitochondrial capacity of the untrained subjects rather well (cf.…”
mentioning
confidence: 99%
“…Estimation of peak quadriceps muscle O 2 utilization (Gifford et al . ), from in vitro mitochondrial respiration data, in patients with COPD is markedly greater (>0.40 l min −1 ) than the V̇normalMO2normalpeak in the current patients with COPD (Gifford et al . , ).…”
Section: Discussionmentioning
confidence: 80%
“…Participants were grouped into those with low aerobic capacity (LO: n = 8, ≤45 mL kg −1 min −1 ), mid‐range (MID, n = 9, 46–55 mL kg −1 min −1 ) and those with high aerobic capacity (HI, n = 7, ≥56 mL kg −1 min −1 ) using similar reference ranges as in a previous study (Gifford et al. ). Analysis of deoxy‐ and total[Hb+Mb] was performed after correction for ATT to a thickness of 0 mm using linear regression of the relationship between total[Hb+Mb] and ATT at rest (Bowen et al.…”
Section: Methodsmentioning
confidence: 99%
“…; Gifford et al. ) and therefore the muscle deoxygenation/fractional O 2 extraction will reach a greater peak in fitter individuals (Ferreira et al. ; Gifford et al.…”
Section: Introductionmentioning
confidence: 99%